Evaluating adequacy of corn nitrogen recommendations in long term cover cropping systems - Sapana Pokhrel; Wade E. Thomason; Amy L. Shober; Rory O. Maguire (Agrosystems, Geosciences & Environment)
Abstract Achieving optimum nitrogen (N) use efficiency in corn (Zea mays L.) production is challenging. We questioned whether Virginia's yield goal (YG)‐based N recommendation (N factor = 17.9 kg Mg−1, the N fertilizer requirement per unit of corn grain yield) adequately accounted for improved N use efficiency under conservation practices including cover crops. We determined the agronomic optimum nitrogen rate and optimum yield at 24 field sites with ≥3 years of cover crops and no‐till to calculate an observed N factor, which was then compared to the yield goal nitrogen (YG‐N) factor. The average observed N‐factor (16.0 kg Mg−1) was not statistically different from YG‐N factor (17.9 kg Mg−1); yet, the observed N‐factor ranged from 5.9 to 37.3 kg Mg−1; 11 of 24 sites would have been over‐fertilized, while seven would have been under‐fertilized if YG‐N factor was applied at these sites (90% confidence interval). Attempted adjustments of the YG‐N factor using single parameters (e.g., cover crop C:N ratio, soil N, and soil nitrate) were insufficient. In contrast, we evaluated N recommendations generated by two open‐source decision support tools (available through PennState Extension and precision sustainable agriculture) that account for cover crops, soil organic matter, and weather parameters. These tools provided more site‐specific, quantitative N recommendations compared to a YG‐based approach, as demonstrated by statistically significant linear relationships between tool‐derived N factors and the observed N factor from our field trials. However, further validation of these open‐source decision support tools is needed to adapt them to regions with different climates and soil conditions.